Modifying Devotional Behavior in the Sunnah of the Prophet - Al-Sharifeen, Emad Abdullah; Abbas, Rami Sami; Al-Azam, Mohammad Nayel (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to clarify the concept of modifying devotional behavior in the prophetic tradition, its forms, and its characteristics. Methods: The researchers used the descriptive approach, analyzing the prophetic hadiths that formed the subject of the research, to reach the most important ideas and findings that serve the study. Results: Among the key findings of the study are the following: the definition of modifying devotional behavior in the prophetic tradition, the mention of the four main forms of modifying devotional behavior, with examples from the prophetic hadith, and the identification of six characteristics that distinguish it. Conclusion: The concept of modifying devotional behavior in the prophetic tradition includes instilling a new devotional behavior, reinforcing an existing devotional behavior by refining and understanding it, or protecting a devotional behavior and ensuring its continuity, as well as addressing and extinguishing any undesirable behavior. The most important prophetic methods for modifying incorrect devotional behavior include: the method of exposure, the method of addressing the motivations behind behavior, the method of direct verbal clarification, the method of direct practical intervention, and the method of punishment. The researchers recommend conducting a study on modifying devotional behavior in the Qur’an and comparing it with the prophetic tradition.